Morphological analysis of the karakalpak language using neural networks (MMIT Proceedings, 2025)
This article explores methods for morphological analysis of the Karakalpak language using neural networks. Karakalpak, a Turkic language with agglutinative morphology, presents challenges for traditional rule-based approaches. We propose architectures based on recurrent (RNN) and transformer (Transformer) networks for tasks such as lemmatization, grammatical category identification, and morpheme segmentation. Quantitative results are presented using the [dataset name] dataset, along with comparisons to classical methods (Finite-State Morphology)